LANGUAGE STYLE ANALYSIS OF KICK ANDY'S TALK SHOW WITH FEMALE GUEST STARS - Sekar Resta Puspitasari; Rosita Ambarwati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
This research aims to find the types of language styles and the frequency of styles used by Kick Andy. The data source in this research is the Kick Andy talk show on Metro TV's official YouTube channel. This research is focused on the style of language used by Kick Andy in his interviews with female guest stars. the author uses a descriptive method that describes the phenomenon based on data sources. This study analyzes the conversations in the interviews to find the types of language styles and language styles that are most often used by Kick Andy. The theory used in this study is the theory of Joss (1998) regarding the types of language style according to their level of formality. The types of language styles are frozen, formal, consultative, casual, and intimate. The results of this study will then reveal which style of language Kick Andy most often uses in his interviews.